Comparison of Cytokine Patterns (IL-6, IL-8, and IL-10) in Influenza and Respiratory Syncytial Virus Infections: An Aage-based Comparative Study - Madfoon, Zainab Mohammed (Medical Science Journal for Advance Research, 2025)
Background: Respiratory viruses such as influenza and respiratory syncytial virus (RSV) remain a global challenge due to the respiratory infections they cause. While both viruses exhibit somewhat similar clinical symptoms, they may elicit different immune responses. Therefore, we compared the patterns of cytokines (IL-6, IL-8, and IL-10) in patients infected with influenza and respiratory syncytial virus (RSV) across different age groups. Methods: 220 samples were collected from patients with respiratory symptoms, 110 of whom were infected with influenza and 75 with RSV. The samples were collected from October 2024 to April 2025 at Al-Zahraa Hospital and Al-Hakim Teaching Hospital, Samples were classified into four groups according to age (≤ 5 years), (6 - 18 years), (19 - 50 years), (≥ 50 years), depending on the maturity of the immune system, the severity of the inflammatory response, and the clinical nfection patterns of each virus. Cytokine levels were measured by ELISA, and statistical analyses were performed using SPSS version 26. Statistical significance was set at a p-value of <0.05. Results: The study results showed a significant difference in elevated levels of IL-6 and IL-8 in patients infected with respiratory syncytial virus (RSV), especially in children under 5 years of age (P < 0.0001), while a significant increase in IL-10 levels was observed in patients infected with influenza virus, particularly in those over 50 years of age (P < 0.01). Conclusion: The differential cytokine patterns imply different immune processes associated with these respiratory viral infections. Influenza appears to induce a greater number of anti-inflammatory processes (IL-10), while RSV induces a greater number of anti-inflammatory processes (IL-8/IL-6). These findings are important for targeted therapeutic approaches and improved clinical management of respiratory viral infections.